China’s Transformation towards a Global Green System of Innovation - Marinova, Dora; Guo, Xiumei; Wu, Yanrui (Emerald, 2013)
Purpose – This paper aims to examine recent trends and China’s role in the emerging global green system of innovation (GGSI) and present the major achievement in China’s R&D sectors and major challenges faced by the country. The authors use China’s role in the clean development mechanism (CDM) as a case to demonstrate the country’s willingness to adopt new technology and green innovation. Design/methodology/approach – In order to understand China’s transformation towards the GGSI, the approach used in this study is a review of innovation systems literature combined with analysis of statistical data from various sources. The authors also build an innovation model for the emerging global green system of innovation to demonstrate the building blocks which allow for transformational system failures to be avoided. The clean development mechanism (CDM) is used as a case example as to how GGSI works. Findings – This paper puts into perspective some recent developments in innovation and argues that there is enough evidence to claim that the world is re-orienting towards a global green system of innovation in which China is already one of the most significant players. Originality/value – Through building a new innovation model, this study demonstrates the complexity and the development of innovation in the context of China’s transformation towards the GGSI.